2020
DOI: 10.1111/asj.13399
|View full text |Cite
|
Sign up to set email alerts
|

Administration of L. salivarius expressing 3D8 scFv as a feed additive improved the growth performance, immune homeostasis, and gut microbiota of chickens

Abstract: Probiotics, which are usually administered in feed, are defined as pure or mixed cultures of live microorganisms that confer beneficial effects on the growth and health of the host by improving the intestinal microbial balance (Brisbin, Gong, Parvizi, & Sharif, 2010). Lactobacillus species, which are gram-positive, nonpathogenic microorganisms found in the human and animal intestinal populations (Amit-Romach, Sklan, & Uni, 2004), are one of the most predominantly used probiotics for health benefits. Several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…A study [ 86 ] on 10-week-old rearing hens suggested that L. salivarius expressing 3D8 scFv can be a potential candidate as a probiotic as it prevents activation of the immune system and maintains immune homeostasis. The oral administration of L. salivarius /3D8 significantly reduced the IL-8, TNF-α, IL-4, IL-1β, IFN-γ, and IGFq expression with this supplementation when the results were compared to the control of the wild-type L. salivarius -treated group of hens.…”
Section: Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…A study [ 86 ] on 10-week-old rearing hens suggested that L. salivarius expressing 3D8 scFv can be a potential candidate as a probiotic as it prevents activation of the immune system and maintains immune homeostasis. The oral administration of L. salivarius /3D8 significantly reduced the IL-8, TNF-α, IL-4, IL-1β, IFN-γ, and IGFq expression with this supplementation when the results were compared to the control of the wild-type L. salivarius -treated group of hens.…”
Section: Immunitymentioning
confidence: 99%
“…L. salivarius expressing 3D8 scFv has been found as beneficial in the study [ 86 ], where it showed the supplementation of that strain increased the abundance of Firmicutes, Proteobacteria, Actinobacterias, and Bacteroides in the fecal samples. Considering the abundance at the genus level, Lactobacillus was found as the most abundant genus, constituting 22.8% of the microbiota in the fecal samples in the L. salivarius 3D8 scFv treated chickens.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Lactobacillus salivarius is a gram-positive bacterium that has been isolated from the breast milk and the cecum of animals [ 16 , 17 ]. So far, several studies have demonstrated the probiotic properties of L. salivarius including the production of natural antibiotics and short chain fatty acids, the reduction of gut pH, and the modulation of gut microbiota [ 16 , 18 ]. In animals, L. salivarius in the chicken diet improved growth performance, boosted immune responses, and attenuated the negative effects of stress [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the IFN-γ, IL-4 , and IL-8 concentrations were significantly reduced in the TG chickens. Sureshkumar et al (2019 , 2020 ) reported significantly reduced levels of the cytokines IL-4 , and IL-4, IL-8, and TNF-1α in chickens fed L. reuteri and L. salivarius expressing the 3D8 scFv gene, respectively. This substantial reduction in cytokines is consistent with the findings of this study, but clear evidence that reduced cytokines were directly involved in whole-body 3D8 scFv gene expression was not confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…3D8 scFv TG chickens showed antiviral activity against H9N2 low-pathogenic avian influenza virus ( AIV ), and further studies showed similar activity against infectious bronchitis virus ( IBV ) and Newcastle disease virus ( NDV ) ( Lee et al, 2019 ; Byun et al, 2020 ). In addition, chickens fed Lactobacillus species expressing 3D8 scFv showed improved growth performance and immune homeostasis ( Sureshkumar et al, 2019 , 2020 ). However, whether whole-body 3D8 scFv gene expression in TG chickens can affect biometric characteristics, such as mortality, growth, and productivity, is unknown.…”
Section: Introductionmentioning
confidence: 99%